Language Symbolization of Memories in T. Morrison’s Novel “Beloved” - I. V. Palashevskaya; S. J. Al-Sammarraie (Научный диалог)
The article is devoted to the study of a literary text from the position of presentational discourse theory, axiological linguistics, conceptology. The means of symbolization of memories in the text of the postmodern novel by T. Morrison “Beloved” as an artistic form of remembering culture, objectification of individual and collective memory of the historical trauma of slavery in the United States are considered. The article analyzes the semiotic types of presentemes of events involved in the appearance of symbolic images with stable semantics and in expression of the text value dominants (LOVE, MEMORY, OBLIVION, LIFE, DEATH, FREEDOM). Signs of the events are revealed (including sound, gustatory, tactile, kinesthetic, artifact, colour and others) described as “triggers” of memories of individual experience, and the keys to restoring the past of the characters. Special attention is paid to signs-locatives -designations of spaces of connection of traumatic images-triggers of memories. The cognitive mechanisms of object connections (metonymic, adjacent, associative), connected by memory, as well as metaphorical stylization of significant experience and relationships are considered. The author distinguishes involuntary memories of characters as acts of the past revival and arbitrary ones in the form of stories as acts of its comprehension, preservation and integration into collective, supra-individual memory. Attention is also paid to the ethical imperatives of attitude to the past (prescriptions of memory, forgiveness, oblivion).